DESIGN IDEA CREATION AND IMPLEMENTATION IN LEARNING PROCESS: STUDY CASE - Veita, Lauma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In the 21st century design thinking or problem-solving methodology has obtained a wide response in product development and service provision. It is a way of thinking which takes us to changes. Currently, in Latvia the schools which implement vocational secondary education art and design education programmes and also vocational orientation education programmes in art and design area have obtained the broadest experience in design acquisition. Taking into account the significance of problem-solving in learners’ development, design has been included in the comprehensive education content. Teachers need a new skill – to organize the design process so that their pupils would acquire problem-solving skills in a practical action. How have the teachers organized the design process? What learning methods have been applied? How is the design thinking developed? Goal analyse theoretical knowledge in design thinking and teachers’ experience of learning technologies in design acquisition which has been acquired in art education of vocational orientation. The Latvian National Culture Centre has compiled the experience of art teachers in methodological material “No Tēla līdz dizainam. Putns” (“From Image to Design. Bird”), it can look at 24 individual or pedagogical workgroup design process methodology for primary school pupils. Using designer IDEO group 3 I model – Inspiration, Ideation, Implementation, in the methodological material, development of design thinking has been described with 10 different techniques. The author’s analysis conveys the possible competences, what knowledge and skills pupils acquire in the design process, what techniques and methods the teacher applies in the learning process in design acquisition. The methodological material used in the research is one of the first for elementary school pupils’ design thinking development in Latvia, it enables us to identify problems and needs for school teachers.